2018
DOI: 10.1177/1045389x18778359
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of uncertainty effects to band gap behavior of circuitry-integrated piezoelectric metamaterial using order-reduced analysis

Abstract: Acoustic metamaterials with unit cells that are integrated with piezoelectric transducer circuitry exhibit interesting band gap behaviors that can be used for wave/vibration manipulation. This research reports the evaluation of uncertainty effects to a typical piezoelectric metamaterial, where uncertainties in geometry/configuration and in circuitry elements are taken into consideration. Monte Carlo-type analysis is performed to assess the band gap features under these uncertainties. In order to facilitate tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…In the context of industrial applications, the material and manufacturing tolerances can also introduce disturbances that affect the periodicity [ 27 , 28 ]. In [ 29 , 30 , 31 ], the influence of uncertainties in periodic structures has been investigated. In order to put the VAMM concept into real-world applications, it is important to quantify the impact of uncertainties in factors such as resonator parameters, the spatial distance between resonators, real-boundary conditions, and non-periodicity on the stop band of the finite VAMM.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of industrial applications, the material and manufacturing tolerances can also introduce disturbances that affect the periodicity [ 27 , 28 ]. In [ 29 , 30 , 31 ], the influence of uncertainties in periodic structures has been investigated. In order to put the VAMM concept into real-world applications, it is important to quantify the impact of uncertainties in factors such as resonator parameters, the spatial distance between resonators, real-boundary conditions, and non-periodicity on the stop band of the finite VAMM.…”
Section: Introductionmentioning
confidence: 99%
“…Since the performance of bandgap formation and the control strategies are strongly dependent on the designed circuit impedance, it creates a strong rationale to investigate its sensitivity and influence due to small variations and disorders. Pan et al [41] investigated the effect of uncertainty on the geometry between the host beam, the piezoelectric transducers and random piezoelectric capacitance on the bandgap formation. They found that the local resonant bandgap behaviour is not much sensitive to different parametric uncertainty configurations but to circuitry parameter uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…31 and 32, whereby ideal periodicity in the formation of the meta-atoms is assumed in the three papers previously mentioned papers on metamaterials. Pan et al 33 discuss the effects of uncertainties in the geometry on the formation of band-gaps of piezoelectric-acoustic metamaterials. Another piece of work on the influence of uncertain stiffness and damping parameters on the properties of acoustic metamaterials was published by Sepahvand and Marburg.…”
Section: Introductionmentioning
confidence: 99%